Corrective lower limb osteotomies in children using temporary external fixation and percutaneous locking plates - Bar-On, Elhanan (Springer Berlin Heidelberg, 2009)
BACKGROUND: We describe a new method for corrective osteotomy and the fixation of lower limb deformities in children. METHODS: Following osteotomy, the desired position is obtained and temporarily stabilized using an external fixator. Definitive fixation is performed with a plate and locking screws inserted percutaneously under fluoroscopic guidance. The procedure was performed in 18 segments in 11 patients. Corrections were performed in all planes. RESULTS: The mean follow up was 18 months (range 6–36 months). All patients were corrected to within 2° of that which was planned. Union was obtained in 16 segments in ten patients within 6–16 weeks. CONCLUSIONS: The method was found to be effective for the correction of deformity in the pediatric population. Advantages compared to conventional methods include minimal soft tissue dissection and the ability to adjust the position before definitive fixation.